2020
DOI: 10.1177/0033294120939844
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Gender, Stress, and Quality of Social Support

Abstract: Background Research suggests that gender differences exist in both stress and how social support is utilized and that the relationship between stress and social support may not be linear. Methods An internet survey of n = 1080 participants was conducted evaluating quality and quantity of social support, gender, age, and perceived stress and coping. Results Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 51 publications
3
32
2
5
Order By: Relevance
“…Furthermore, in a strongly patriarchal society such as China, women in marriage rely heavily on their husbands' status, power, and social resources, and are more affected by the changes caused by widowhood (92)(93)(94). In contrast, compared to women, elderly males have smaller social networks and are less likely to initiate or engage in social outdoor activities (52). Thus, widowhood has little effect on changes in social network size for elderly males, and the mediating role of social support is not significant either.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a strongly patriarchal society such as China, women in marriage rely heavily on their husbands' status, power, and social resources, and are more affected by the changes caused by widowhood (92)(93)(94). In contrast, compared to women, elderly males have smaller social networks and are less likely to initiate or engage in social outdoor activities (52). Thus, widowhood has little effect on changes in social network size for elderly males, and the mediating role of social support is not significant either.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Men and women may receive different types and levels of social support, which may result in different outcomes in health ( 52 ). For example, a study found that men benefit from social support in terms of improved mental health, while women benefit from social support in terms of improved physical health ( 53 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both male and female athletes benefit from having supportive teammate relationships (Scott et al, 2020). A recent study indicated that males reported smaller social support networks and less quality in their social support (Kneavel, 2020). Additionally, while male athletes have reported more sources of social support, female athletes reported relying on friends for social support more frequently and having greater satisfaction with their social support (Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al 42 found that male students reported higher levels of stress. However, Ng and Jeffery, 43 Shaw et al, 44 and Kneavel 45 reported that females were more likely to be stressed than males. Most recently, we reported that student-perceived stress levels increased substantially (18%) after 6 months in our institution's chiropractic training program compared with the 1st week of the program (t 406 ¼ 6.32, p , .001, d ¼ .33).…”
Section: Student-perceived Stressmentioning
confidence: 98%